2018
DOI: 10.1124/dmd.118.084301
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Experimental Conditions of Automated Glucuronidation Assays in Human Liver Microsomes Using a Cocktail Approach and Ultra-High Performance Liquid Chromatography–Tandem Mass Spectrometry

Abstract: UDP-glucuronosyltransferase (UGT)-mediated metabolism is possibly the most important conjugation reaction for marketed drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The glucuronide formation rates of selected UGT probe substrates were determined using individual and pooled microsomal liver preparations within a single experiment using a Tecan Fluent system and under optimized experimental conditions similar to those described in our previous study . For substrates exhibiting high turnover rates, the quality and reliability of in vitro measurements were confirmed by the lack of depletion of parent substrate, which was monitored in parallel to glucuronide formation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The glucuronide formation rates of selected UGT probe substrates were determined using individual and pooled microsomal liver preparations within a single experiment using a Tecan Fluent system and under optimized experimental conditions similar to those described in our previous study . For substrates exhibiting high turnover rates, the quality and reliability of in vitro measurements were confirmed by the lack of depletion of parent substrate, which was monitored in parallel to glucuronide formation.…”
Section: Discussionmentioning
confidence: 99%
“…24 Selective or partially selective substrates of hepatic UGT isoforms were previously discussed in our recent study. 24 Oxazepam was incubated as a mixture of Sand R-stereoisomers. Stereoselective analysis demonstrated that S-oxazepam glucuronide represented the main glucuronide metabolite (50%−91% of total concentration) in the microsomal incubations (inhouse data), and therefore S-oxazepam glucuronide formation was used to assess the microsomal glucuronidation activity of UGT2B15.…”
Section: Selection and Incubation Of Ugt Probe Substratesmentioning
confidence: 93%
See 3 more Smart Citations